2012
DOI: 10.1063/1.3665968
|View full text |Cite
|
Sign up to set email alerts
|

Low energy beam transport for facility for rare isotope beams driver linear particle accelerator

Abstract: The driver linac for the facility for rare isotope beams (FRIB) will provide a wide range of primary ion beams for nuclear physics research. The linac will be capable of accelerating a uranium beam to an energy of up to 200 Mev∕u and delivering it to a fragmentation target with a maximum power of 400 kW. Stable ion beams will be produced by a high performance electron cyclotron resonance ion source operating at 28 GHz. The ion source will be located on a high voltage platform to reach an initial beam energy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Each ion source has its associated LEBT line and the lines merge into one connecting with the RFQ. A similar structure can be found in Spiral-2 [5] at GANIL and FRIB [6] at MSU. After each charge selection section of the sources, a set of diagnostic devices, including two Allison-type emittance meters, a Faraday cup and a fluorescent target, are available.…”
Section: Hiaf Front Endsupporting
confidence: 66%
“…Each ion source has its associated LEBT line and the lines merge into one connecting with the RFQ. A similar structure can be found in Spiral-2 [5] at GANIL and FRIB [6] at MSU. After each charge selection section of the sources, a set of diagnostic devices, including two Allison-type emittance meters, a Faraday cup and a fluorescent target, are available.…”
Section: Hiaf Front Endsupporting
confidence: 66%
“…In the simulation, we assumed all ion species have the same initial conditions with a emittance of 100 π mm mrad and Twiss parameters α = −0.5, β = 173 mm/mrad. 3 Effect of space charge has been studied and discussed in previous works, 2 indicated that such a low energy beam is very sensitive to it. However, there has not been an effective method to increase the space charge compensation for high charged ion beams.…”
Section: Simulated and Experimental Resultsmentioning
confidence: 99%
“…The Low Energy Beam Transport (LEBT) [11] was designed to transport two-charge-state heavy-ion beams from the ion source to the linac with high reliability and high beam quality. To produce a small longitudinal emittance, the direct-current (dc) beam from the ion source is bunched upstream of -7 - The concept of bunching a dual-charge-state beam and injection into the RFQ is detailed in ref.…”
Section: Velocity Equalizermentioning
confidence: 99%